1997
DOI: 10.1029/96ja04002
|View full text |Cite
|
Sign up to set email alerts
|

Bow shock analysis at comets Halley and Grigg‐Skjellerup

Abstract: Abstract. The interaction of an active comet with the solar wind is effected by the pickup of heavy cometary ions over extended regions of space. It was predicted before any spacecraft encounters with comets that a bow shock would form at a critical point in the mass-loaded flow. Here we present an analysis of the results from Giotto's encounters of comets Halley and Grigg-Skjellerup on the plasma structure of the bow shock regions at the two comets. This is achieved in a joint analysis of data on solar wind a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Halley, with the largest neutral production rate of the three, affected SW plasma out to distances of 5 x 106 km [Gringauz et at., 1986], compared to a pickup ion gyroradius of • 104kin [SzegS, 1988], and had several plasma boundaries, some open to interpretation. Grigg-Skjellerup represented the interaction at a much smaller source, and consequently was found to have fewer boundaries and a weaker shock-like interaction, such that on the inbound pass it was interpreted as a bow "wave" [Coates et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Halley, with the largest neutral production rate of the three, affected SW plasma out to distances of 5 x 106 km [Gringauz et at., 1986], compared to a pickup ion gyroradius of • 104kin [SzegS, 1988], and had several plasma boundaries, some open to interpretation. Grigg-Skjellerup represented the interaction at a much smaller source, and consequently was found to have fewer boundaries and a weaker shock-like interaction, such that on the inbound pass it was interpreted as a bow "wave" [Coates et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's bow shock was discovered in 1964 (Ness et al 1964) and subsequently, bow shocks have been observed at all of the visited planets (Treumann and Jaroschek 2008), at comet Halley (Coates et al 1997), and, most recently, at the termination shock that separates the solar system from interstellar space (see for example, Stone et al 2005). Soon after the Earth's bow shock was discovered, Kaufmann (1967) noted that some shock transitions from upstream to downstream were sharp and well defined, while others were noisy and accompanied by large magnetic fluctuations.…”
Section: Bow Shock Studiesmentioning
confidence: 99%
“…The mass loading associated with these slows the plasma enough that eventually a bow shock forms. Pickup ions play a key role at the bow shock [26,27,28].…”
Section: Pickup Ions Dominate the Comet-sw Interactionmentioning
confidence: 99%